Water Quality and Fish Diversity of Bagmati River in Kathmandu Valley - Rijal, Bishwanath; Adhikari, Tulsi Raj; Adhikari, Sakar; Lamichhane, Sandesh; Baral, Suraj (Journal of Institute of Science and Technology, 2025)
This study assesses the water quality and aquatic habitat in various sites of the Bagmati River in Kathmandu Valley. This study was carried out between February and June across an urban gradient in the Bagmati River of Kathmandu Valley. We used a D-frame net of 90cm by dipping-net in the benthic zone maintaining a walking distance of 20 m and repeating the same process four times (two times at each bank of the river) on each site on each visit. Schizothorax labiatus (Snow Trout), Schistura beavani (Ring Loach), Esomus danrica (Flying barb), Glyptosternum maculatum (Torrent Catfish) and Channa orientalis (Asiatic snakehead) were various fish species found during our study. The maximum Biological oxygen demand (BOD) was observed from Teku and the lowest from Shivapuri. The minimum and maximum dissolved Oxygen recorded was at Sundarijal. The pH ranged from 7 to 7.4 in Sundarijal. The minimum conductivity was found in Sundarijal, whereas the maximum was found in Teku. The maximum turbidity was observed at Teku and the lowest at Sundarijal. Maximum alkalinity was observed at Teku and lowest at Shivapuri. The fish diversity and water quality were affected by urbanization. We recommend the study be conducted southwards to determine the impact urbanization has on the lotic ecosystem.